New perspectives on Microsoft Windows 98 for power users - Phillips, Harry L. (Course Technology, 1999)
This book is about: The Windows 98 Operating System; Customizing Windows 98; Exploring the Windows 98 Filing System; Implementing Shortcut Strategies; Using OLE Technologies; Safeguarting Your Computer; Using Troubleshooting Tools; Evaluating System Performance...